Investigating the role of IL-4/IL-13 and their receptors in ulcerative colitis - Hoving, J Claire (Department of Clinical Laboratory Sciences, 2014)
Ulcerative colitis (UC) is a heterogeneous inflammatory bowel disease (IBD) associated with chronic inflammation of the gastrointestinal tract. Characterized by genetic and immunological abnormalities, UC has overly aggressive T-cell responses to commensal bacteria eventually leading to disease pathology. UC is distinguished from Crohn's disease, another form of IBD, in that it is driven by a T helper type 2 (Th2) immune response. Oxazolone-induced colitis is a mouse model resembling UC presenting with inflammation limited to the distal colon and mixed neutrophil/lymphocyte infiltration in the superficial layer of the mucosa. The Th2 cytokines interleukin (IL)-4 and IL-13 are associated with the onset of oxazolone colitis and both signal through a common IL-4 receptor-alpha chain (IL-4R +-). Neutralizing these cytokines prevents or ameliorates disease significantly, while neutralizing IL-12 exacerbates disease symptoms. As many aspects of the mechanisms involving Th2 cytokines in colitis remain undefined, the aim of this study was to investigate the role of IL-4 and IL-13 and the receptors through which they signal in oxazolone-induced colitis. Previous studies have highlighted a role for IL-4 and IL-13 in mediating oxazolone colitis. We show that while IL-13-deficient BALB/c mice were protected from disease onset, IL-4R +- deficient BALB/c mice developed exacerbated disease symptoms.